Teknik Dan Pertimbangan Efektif Dalam Peningkatan Mutu Pendidikan Berbasis Data - Nanda Aprilia; Agus Salim Salabi (Jurnal Manajemen Pendidikan, 2026)
Objective: This study explores effective techniques and key considerations in data-driven quality improvement of education through a case study at MAS Jabal Nur. Employing a qualitative case study approach, data were gathered through in-depth interviews and document analysis. The findings reveal that the principles of Data-Driven Decision Making (DDDM) have been systematically applied, including academic performance analysis, curriculum evaluation, and the use of a dashboard-based monitoring system. Three key indicators outcome, process, and perception were used to assess effectiveness, all of which demonstrated improvements in student achievement, teacher and student engagement, and stakeholder satisfaction. However, challenges persist, particularly in terms of limited data literacy among teachers and underdeveloped technological infrastructure. These findings affirm the strategic role of data in educational decision-making, while highlighting the need for investment in human resource capacity, a collaborative organizational culture, and integrated information systems. This research contributes to the development of evidence-based quality management models, especially within Islamic educational institutions.